Elastolytic Mechanism of a Novel M23 Metalloprotease Pseudoalterin from Deep-sea Pseudoalteromonas sp. CF6-2: CLEAVING NOT ONLY GLYCYL BONDS IN THE HYDROPHOBIC REGIONS BUT ALSO PEPTIDE BONDS IN THE HYDROPHILIC REGIONS INVOLVED IN CROSS-LINKING - Zhao, Hui-Lin (American Society for Biochemistry and Molecular Biology, 2012)
Elastin is a common insoluble protein that is abundant in marine vertebrates, and for this reason its degradation is important for the recycling of marine nitrogen. It is still unclear how marine elastin is degraded because of the limited study of marine elastases. Here, a novel protease belonging to the M23A subfamily, secreted by Pseudoalteromonas sp. CF6-2 from deep-sea sediment, was purified and characterized, and its elastolytic mechanism was studied. This protease, named pseudoalterin, has low identities (<40%) to the known M23 proteases. Pseudoalterin has a narrow specificity but high activity toward elastin. Analysis of the cleavage sites of pseudoalterin on elastin showed that pseudoalterin cleaves the glycyl bonds in hydrophobic regions and the peptide bonds Ala–Ala, Ala–Lys, and Lys–Ala involved in cross-linking. Two peptic derivatives of desmosine, desmosine-Ala-Ala and desmosine-Ala-Ala-Ala, were detected in the elastin hydrolysate, indicating that pseudoalterin can dissociate cross-linked elastin. These results reveal a new elastolytic mechanism of the M23 protease pseudoalterin, which is different from the reported mechanism where the M23 proteases only cleave glycyl bonds in elastin. Genome analysis suggests that M23 proteases may be popular in deep-sea sediments, implying their important role in elastin degradation. An elastin degradation model of pseudoalterin was proposed, based on these results and scanning electron microscopic analysis of the degradation by pseudoalterin of bovine elastin and cross-linked recombinant tropoelastin. Our results shed light on the mechanism of elastin degradation in deep-sea sediment.